Ferrostatin-1 inhibits osteoclast differentiation and prevents osteoporosis by suppressing lipid peroxidation - Wenbo Xu; Shiyan Lv; Xiaoyan Wang; Chengchao Song; Chunyang Xi; Jinglong Yan (Journal of Orthopaedic Surgery and Research)
Abstract Background Osteoporosis (OP) is a systemic disease characterized by low bone mass. New progress has been made in the study of OP, such as lipid peroxidation. However, the role of lipid peroxides in osteoclast differentiation is still unclear. Methods Bone marrow macrophages (BMMs) were extracted from C57BL/6J mice and induced to differentiate into osteoclasts, which were observed via TRAP staining, Phalloidin staining and bone pit assays. Related substances of lipid peroxidation were detected during osteoclastogenesis. The levels of osteoclastogenesis and lipid peroxides were measured by qRT-PCR, Western Blot and immunofluorescence. Activation of the p38/JNK/MAPK pathway was detected by Western Blot. The capacity for osteogenesis and angiogenesis of cells after treatment with supernatant of BMMs was evaluated. Furthermore, Ferrostatin-1 (Fer-1), from which femur and serum samples were comprehensively evaluated, was used in OVX mice. Results During osteoclastogenesis, the levels of ROS, MDA, ACSL4 and LPCAT3 increased with increasing duration of RANKL stimulation, while there were no significant changes in the levels of GSH or GPX4. Fer-1 inhibited osteoclast differentiation and decreased the level of lipid peroxides. In addition, Fer-1 inhibited osteoclast-related markers by inhibiting the p38/JNK/MAPK pathway. Furthermore, the supernatant of BMMs after Fer-1 treatment promoted osteogenesis and angiogenesis. Finally, Fer-1 successfully alleviated OP in OVX mice by reducing the level of lipid peroxidation in vivo. Conclusion Fer-1 suppresses osteoclast differentiation by reducing lipid peroxidation levels regulated by ACSL4, which is mediated through the p38/JNK/MAPK signaling pathway. Additionally, Fer-1 enhances the coupling between osteogenesis and angiogenesis and has an anti-OP effect in vivo.